Landscaping Backyards for Wildlife: Top Ten Tips for Success - Mark E. Hostetler; Gregg Klowden; Sarah Webb Miller; Kara N. Youngentob (EDIS, 2003)
This document is Circular 1429, one of a series of the Department of Widlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published in January 2003.